Struktur Kecepatan Gelombang Geser (Vs) di Daerah Rawan Gerakan Tanah (Longsor) Jalan Lintas Kabupaten Bengkulu Tengah-Kepahiang - Nanang Sugianto; Refrizon Refrizon (Department of Physics, Sebelas Maret University, 2021)
Shear wave velocity (Vs) structure at along of Central Bengkulu-Kepahiang crossline has been mapped. This research aims to identify the subsurface structure and to estimate the constituent material type of rock in landslide-prone areas (Central Bengkulu-Kepahiang crossline). Shear wave velocity structure on each site is obtained by the HVSR-inversion of 146 microtremor data (ambient noise recording of seismometer). Vs structure at the line mapped from the surface until to 30 meters of the depth. Groups of Vs are identified in class E (Vs <180), Class D (180≤ Vs <360), Class C (360≤ Vs <760), and Class B (760≤ Vs <1500). The subsurface structure at the depth of 0 to 10 meters are dominated by stiff soil, very dense soil, and soft rock which has highly fractured and weathered rock properties. At the depth of 15 meters to 30 meters, the subsurface structure is dominated by hard rock but it is high potential or easy to fracturing and weathering like the properties of the rocks in areas that have landslides in the past. Based on Vs value, rock constituent materials are deposition of sand, clay, gravel and alluvium ranging from soft to relatively hard structures at the depth.